PENGELOLAAN MANAJEMEN KESEHATAN TIDAK EFEKTIF DENGAN PROMOSI KESIAPAN PENERIMAAN INFORMASI PADA KELUARGA DENGAN DIABETES MELITUS DI PUSKESMAS DUREN KABUPATEN SEMARANG - Pipit Kusumaningrum; Ummu Muntamah (Jurnal Kesehatan, 2025)
Diabetes melitus is a heterogeneous group of disorders characterized by increased blood glucose levels or hyperglycemia. Glucose normally circulates in a certain amount in the blood, glucose is formed in the liver from the food consumed. Because of that, the nursing problem of Improved Health Management Readiness arose. Writing aims to provide an overview of readiness to improve health management in families with diabetes mellitus. The method in this study used the description method, namely to provide an overview of the knowledge and treatment of gout. Management in the family is carried out for 3 days starting with assessment, diagnosis, intervention, implementation, and evaluation. The results of the nursing evaluation showed that patient data was able to explain the definition, signs and symptoms of diabetes in their own language, such as “diabetes is an increase in blood sugar, frequent urination, frequent drinking”. Patients and families say that patients have reduced sweet drinks such as tea, syrup and watermelon. The client says he is already taking medication. Patients are able to answer correctly when asked about diabetes mellitus. The medication control booklet is filled. At the end of the management, the author hopes that the results of this research will be useful as a reference during the learning process so that knowledge about nursing care for families with diabetes mellitus can be carried out optimally.